Pengembangan Media Video Pembelajaran Menggunakan Aplikasi Capcut dalam Materi Cahaya pada Siswa Kelas III SD Kartika XVII-1 Pontianak Kota: Penelitian - Arista, Tantri; Hairida, Hairida; Salimi, Asmayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to produce Learning Video Media Using the Capcut Application on Light Material for grade III students of SD Kartika XVII-1 Pontianak City which can be used to help science learning activities. the model used in this study is the 4D model. The sources of this study were homeroom teachers, 22 grade III students of SD Kartika XVII-1 Pontianak City, and 3 expert validators, namely lecturers. The data collection technique for this study was in the form of student questionnaires/responses. The results of the study showed that the development of Learning Video Media Using the CapCut Application had gone through 4 research steps, namely define, design, development, and disseminate. The results of the study showed that: (1) The validity of the learning media by expert validators obtained a value from the validator including, media aspects 3.8 with the category "valid", language aspects 3.1 with the category "valid" and design and material aspects 3.4 with the category "valid". (2) The feasibility of the media based on student responses obtained a score of 88.04 with the category "very feasible" and teacher responses obtained a score of 4.8 with the category "very feasible". Based on the feasibility assessment, the learning video media obtained good results from teachers and students so that it is suitable for use as a learning medium.